PROSES AFIKSASI BAHASA JAWA DIALEK BANYUMAS (SUATU KAJIAN MORFOLOGI) - nurdiyanto1, erwita1 (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2016)
The process of addition is part of a study of the morphology, namely the study of the shape of the rules of the language. The addition process is the process of formation of words from another entity which is a basic form. Java language dialect Banyumas has affixes, whether it be a prefix, suffix, and inserts a word-forming element. In this study, which became the object of study is the Java language dialect Banyumas by scrutinizing how the process of addition in Javanese dialect Banyumas and certainly aimed to describe the process of addition in Javanese dialect Banyumas. The method used in the data analysis method used in this study distributional-reflective and introspective method. From the analysis, the addition in Javanese dialect Banyumas includes the process of affixation, reduplication process, and the process of compounding. Affixation process is divided into four kinds, namely prefiksasi process, infiksasi, sufiksasi, and konfiksasi. The process of compounding the Java language dialect Banyumas in terms of basic shapes are combined distinguished syllabic merging and merging intact. Judging from the relationship schematically basic elements distinguished on a single identical compounding, compounding synthetic, semi-synthetic compounding. Judging from the level of relations between the forms is basically divided on equal compounding, compounding explained explained, and compounding that the merger serves to form adjectives, in this case can be distinguished according to the true meaning and figurative sense